Landscape Patterns of Wetland Parks in Suzhou based on ArcGIS and Fragstats: a Case Study of Huqiu Wetland Park and Taihu Hubin National Wetland Park. Issue 1 (February 2021) - Bi, Yu; Ma, Jianwu; Li, Shuangqi
Abstract: Taking Huqiu Wetland Park and Taihu Hubin National Wetland Park as the study objects, ArcGIS and Fragstats techniques were used to analyze the landscape pattern characteristics of the two parks in terms of patch type and landscape level. The results showed that the landscape types of both Huqiu Wetland Park and Taihu Hubin National Wetland Park were dominated by wetlands, accounting 37.7% and 82.24% of the total park area of the pars respectively. The aggregation index were 99.72 and 99.96 respectively, and the aggregation of wetland patches in Taihu Hubin National Wetland Park was higher. The percentages of grassland and built-up area were higher in Huqiu Wetland Park than in Taihu Hubin National Wetland Park, but plaque agglomeration was lower than that in Taihu Hubin National Wetland Park. In terms of landscape diversity, Huqiu Wetland Park's Shannon Diversity Index of 1.33 and Shannon Uniformity Index of 0.83 were both higher than Taihu Hubin National Wetland Park's 0.63 and 0.45, indicating that dominant landscape was not sufficiently prominent and that the patch. The differences in landscape patterns between the two wetland parks are related to their planning design, regional location, surrounding environment and human disturbance.